METHODOLOGY FOR SOCIO-ENVIRONMENTAL ANALYSIS OF DOMICILES PRESENTS IN WATERSHEDS - Silva, D. C. Cunha E. [UNESP] (2019)
Socio-environmental indicators are important mechanisms for the communication of summary information or for the provision of solid bases on the quality of life of human beings. Therefore, in this study was elaborated a Household Quality Indicator (HQI), that integrated socio-environmental information from the Una River Watershed, using in your calculation demographic census data and geoprocessing techniques. This indicator ranges from 0 to 1, where 0 represents the most undesirable condition while 1 represents the desirable condition. All the census tracts present in the rural area in the study area had HQI values lower than 0.5 and were classified as inadequate, while almost all the census tracts present in the urban area presented values higher than 0.5 and, therefore, were classified as excellent. The areas classified as inadequate represent 76,4% of the study area. These lower than expected values are justified by the poor sanitation conditions present in the study area. The urban area compared to the rural area showed the best HQI values, justified by the population access to the best conditions of basic sanitation.